Scenes from the epic life of a total genius - Matson, Stacey (Naperville, Illinois : Sourcebooks Jabberwocky, 2016)
"Eighth-grader Arthur Bean's life has taken a turn for the adventurous--two girlfriends to deal with, and a blockbuster film to co-write, produce and direct. How crazy can one school year get? Told through emails, doodles, texts, newspaper articles, and AV Club rules"--
Originally published in Toronto by Scholastic Canada in 2015.
Sequel to: A year in the life of a complete and total genius.
Accelerated Reader
Junior Library Guild selection.
Keywords: Motion pictures -- Production and direction -- Fiction; Authorship -- Fiction; Dating (Social customs) -- Fiction; Junior high schools -- Fiction; High schools -- Fiction; Humorous stories; Canada -- Fiction; High schools -- fiction; Dating (Social Customs) -- Fiction; Humorous stories; Motion pictures -- Production and direction -- Fiction; Canada -- Fiction; Epistolary fiction; Humorous fiction; Juvenile works